2012
DOI: 10.1177/0148558x11409158
|View full text |Cite|
|
Sign up to set email alerts
|

Managerial Stock Ownership, Analyst Coverage, and Audit Fee

Abstract: The authors study whether managerial ownership and analyst coverage relate to audit fees. To the extent that these corporate governance factors relate to auditor assessment of the firm’s agency costs and hence various risks the auditor must consider in the development of an audit program, they will affect audit effort and hence audit fees. The authors find that managerial equity holdings and analyst coverage are negatively associated with audit fees and that these associations are both statistically and econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
55
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 58 publications
6
55
2
4
Order By: Relevance
“…For example, Doukas, McKnigh, and Pantzalis (2005) and Jung, Sun, and Yang (2012) suggest that financial analysts facilitate more effective monitoring of the firms' activities, thereby reducing agency costs and increasing share value. Moreover, Baik, Kang, and Morton (2010) and Gotti, Han, Higgs, and Kang (2012) show that more analysts following increases firm value and reduces audit fees. In addition, Lang, Lins, and Maffett (2012) document higher liquidity and lower transaction costs when the number of analysts following a firm is higher.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Doukas, McKnigh, and Pantzalis (2005) and Jung, Sun, and Yang (2012) suggest that financial analysts facilitate more effective monitoring of the firms' activities, thereby reducing agency costs and increasing share value. Moreover, Baik, Kang, and Morton (2010) and Gotti, Han, Higgs, and Kang (2012) show that more analysts following increases firm value and reduces audit fees. In addition, Lang, Lins, and Maffett (2012) document higher liquidity and lower transaction costs when the number of analysts following a firm is higher.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, prior literatures find that there is a negative association between analyst coverage and audit fee in U.S. or China. This argument supports that analyst coverage plays a role of corporate governance to constrain manager's opportunistic earnings management behavior (Gotti et al, 2011;Haw et al, 2012).…”
Section: Introductionmentioning
confidence: 72%
“…Yu (2008) finds that analysts are capable and resourceful in tracking firms regularly, and they continuously scrutinize management behavior and financial reporting irregularities. Gotti et al (2011) suggest that the existence of a negative relationship between analyst coverage and audit fees using U.S. data from 2000 to 2007. The study supports analysts' monitoring hypothesis that analysts are one of external corporate governance mechanism to monitor managers' earnings management.…”
Section: Introductionmentioning
confidence: 99%
“…Abernathy, Kang, Krishnan, and Wang () found that the higher the residual audit fees, the lower the analyst forecast accuracy, which means that it is more difficult to forecast earnings for that company, thus indicating poor earnings quality. In spite of the above, Gotti, Han, Higgs, and Kang () found that managerial equity ownership is associated with lower audit fees because management and shareholder interests are aligned. They also stated that the extent of analyst following is associated with lower audit fees (Gotti et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…In spite of the above, Gotti, Han, Higgs, and Kang () found that managerial equity ownership is associated with lower audit fees because management and shareholder interests are aligned. They also stated that the extent of analyst following is associated with lower audit fees (Gotti et al, ). Deis, Byus, Lelkes, and Reed () analyzed audit fees and audit firm tier for oil and gas companies and found that oil and gas companies have begun to move away from the Big 4 Audit Firms and to the Regional and Local Firms where the audit fees are lower.…”
Section: Introductionmentioning
confidence: 97%